2015
DOI: 10.5946/ce.2015.48.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Effectiveness of Oral Phloroglucin and Cimetropium Bromide as Premedication for Diagnostic Esophagogastroduodenoscopy: An Open-Label, Randomized, Comparative Study

Abstract: Background/AimsSuppression of gastrointestinal (GI) peristalsis during GI endoscopy commonly requires antispasmodic agents such as hyoscine butylbromide, atropine, glucagon, and cimetropium bromide. This study examined the efficacy of oral phloroglucin for the suppression of peristalsis, its impact on patient compliance, and any associated complications, and compared it with intravenous or intramuscular cimetropium bromide administration.MethodsThis was a randomized, investigator-blind, prospective comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
2
4
0
Order By: Relevance
“…Most adverse events were mild and spontaneously resolved with no additional management requirement. These findings are consistent with a previous study that demonstrated no serious adverse events during the study period [ 14 ]. Furthermore, the incidence of dry mouth was significantly lower in patients treated with phloroglucinol than in those treated with cimetropium bromide during diagnostic EGD [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Most adverse events were mild and spontaneously resolved with no additional management requirement. These findings are consistent with a previous study that demonstrated no serious adverse events during the study period [ 14 ]. Furthermore, the incidence of dry mouth was significantly lower in patients treated with phloroglucinol than in those treated with cimetropium bromide during diagnostic EGD [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…Before the study, the efficacy of oral phloroglucinol as a premedication for EGD had not been extensively evaluated. Only one study compared the suppression of peristalsis during diagnostic EGD between oral phloroglucinol and intravenous cimetropium bromide [ 14 ]. Oral phloroglucinol was inferior to cimetropium bromide in inhibiting gastric peristalsis, but the difference was not clinically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cimetropium bromide is widely used to inhibit peristalsis and improve visualization during colonoscopy in South Korea. [ 30 ] The antispasmodic effect of cimetropium bromide begins promptly (within 1 minute) after injection and has a half-life of 50 minutes. [ 31 ] Cimetropium-related side effects include mild tachycardia and dry mouth.…”
Section: Discussionmentioning
confidence: 99%